Avaliacão da satisfação do usuário e da qualidade dos tratamentos endodônticos em Centros de Especialidades Odontológicas da Grande Natal-RN - Pontes, Anna Leprincia Bezerra (2011)
Objective: To evaluate the degree of users satisfaction and technical quality of endodontic treatment in specialized dental clinics (CEO) of Grande Natal / RN between 2006 and 2008. Methodology: evaluated 282 endodontically treated teeth in CEOs through clinical and radiographic examinations. A questionnaire about the clinical condition of the tooth, evaluation of care and satisfaction with treatment was applied. Data on pre-and trans-operative were noted by the patient's clinical record. Endodontically treated teeth were examined by a specialist in endodontics, which compared with previous radiographs and current ones. The collected datas were presented descriptively by absolute numbers, percentages, averages. To determine the association between the independent and dependent variables was carried out through the bivariate association test Chi-square and Fisher exact test. Results: 79.8% presented with radiographic normal and 84.4% without pain symptoms. 8.2% of the teeth were fractured and 3.2% extracted. The persistence of the periapical lesion was associated with initial periapical status (p <0.05). 91.5% of patients are satisfied with the outcome of treatment. Such satisfaction is associated with absence of pain and an adequate esthetic tooth position (p <0.05). Conclusion: endodontic treatment in specialized dental clinics have an adequate technical quality, resulting in the success of endodontic therapy performed in these centers and that users are satisfied with the treatment